A Longitudinal Electromyography Study of Complex Movements in Poststroke Therapy. 1: Heterogeneous Changes Despite Consistent Improvements in Clinical Assessments - Hesam-Shariati, Negin; Trinh, Terry; Thompson-Butel, Angelica G.; Shiner, Christine T.; McNulty, Penelope A. (Frontiers in Neurology, 2017)
Poststroke weakness on the more-affected side may arise from reduced corticospinal drive, disuse muscle atrophy, spasticity, and abnormal coordination. This study investigated changes in muscle activation patterns to understand therapy-induced improvements in motor-function in chronic stroke compared to clinical assessments and to identify the effect of motor-function level on muscle activation changes. Electromyography (EMG) was recorded from five upper limb muscles on the more-affected side of 24 patients during early and late therapy sessions of an intensive 14-day program of Wii-based Movement Therapy (WMT) and for a subset of 13 patients at 6-month follow-up. Patients were classified according to residual voluntary motor capacity with low, moderate, or high motor-function levels. The area under the curve was calculated from EMG amplitude and movement duration. Clinical assessments of upper limb motor-function pre- and post-therapy included the Wolf Motor Function Test, Fugl-Meyer Assessment and Motor Activity Log Quality of Movement scale. Clinical assessments improved over time (p < 0.01) with an effect of motor-function level (p < 0.001). The pattern of EMG change by late therapy was complex and variable, with differences between patients with low compared to moderate or high motor-function levels. The area under the curve (p = 0.028) and peak amplitude (p = 0.043) during Wii-tennis backhand increased for patients with low motor-function, whereas EMG decreased for patients with moderate and high motor-function levels. The reductions included movement duration during Wii-golf (p = 0.048, moderate; p = 0.026, high) and Wii-tennis backhand (p = 0.046, moderate; p = 0.023, high) and forehand (p = 0.009, high) and the area under the curve during Wii-golf (p = 0.018, moderate) and Wii-baseball (p = 0.036, moderate). For the pooled data over time, there was an effect of motor-function (p = 0.016) and an interaction between time and motor-function (p = 0.009) for Wii-golf movement duration. Wii-baseball movement duration decreased as a function of time (p = 0.022). There was an effect on Wii-tennis forehand duration for time (p = 0.002), an interaction of time and motor-function (p = 0.005) and an effect of motor-function level on the area under the curve (p = 0.034) for Wii-golf. This study demonstrated different patterns of EMG changes according to residual voluntary motor-function levels, despite heterogeneity within each level that was not evident following clinical assessments alone. Thus, rehabilitation efficacy might be underestimated by analyses of pooled data.